Mengasuh Anak dengan Cinta dan Kasih Sayang dalam Perspektif Psikologi Islam - Dian Ayu Puspita Sari Nst; Nurmala Siregar; Nursyamsiah Simbolon; Masganti Sit (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The development of the modern world, characterized by advances in digital technology, globalization, and complex social dynamics, has created new challenges in child-rearing practices, particularly for Muslim families. Children require not only the fulfillment of physical needs and formal education, but also balanced emotional, social, and spiritual support. This study aims to examine the concept of child-rearing based on love and compassion from the perspective of Islamic psychology, identify the core principles of Islamic parenting, and explain its implications for children’s psychological development. This research employed a qualitative approach using a literature review method with a systematic literature review design. Data sources were obtained from academic books as well as nationally accredited journals and reputable international journals published between 2020 and 2024. The data were analyzed using content analysis and thematic analysis to identify patterns, key concepts, and relationships among variables. The findings indicate that parenting grounded in love and compassion (rahmah), combined with role modeling, justice, and wisdom in discipline, contributes positively to children’s emotional, social, moral, and spiritual development. Warm and responsive Islamic parenting supports the development of effective emotional regulation, prosocial behavior, and the internalization of faith-based and moral values in children. The results also demonstrate a strong alignment between Islamic parenting concepts and the compassionate parenting approach in modern psychology, with Islamic psychology offering a distinctive strength in its spiritual dimension. This study contributes to the reinforcement of the theoretical framework of Islamic psychology and provides practical recommendations for parents and educators in implementing balanced parenting that integrates compassion, discipline, and Islamic values in the modern era.